2005
DOI: 10.1128/jvi.79.8.4991-4999.2005
|View full text |Cite
|
Sign up to set email alerts
|

Enfuvirtide Resistance Mutations: Impact on Human Immunodeficiency Virus Envelope Function, Entry Inhibitor Sensitivity, and Virus Neutralization

Abstract: Enfuvirtide (ENF/T-20/Fuzeon), the first human immunodeficiency virus (HIV) entry inhibitor to be licensed, targets a structural intermediate of the entry process. ENF binds the HR1 domain in gp41 after Env has bound CD4, preventing conformational changes needed for membrane fusion. Mutations in HR1 that confer ENF resistance can arise following ENF therapy. ENF resistance mutations were introduced into an R5-and X4-tropic Env to examine their impact on fusion, infection, and sensitivity to different classes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
122
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(137 citation statements)
references
References 53 publications
13
122
1
1
Order By: Relevance
“…As previous reports for other entry inhibitors (Berro et al, 2009;Pugach et al, 2008;Reeves et al, 2005; Yoshimura et al, 2014), we showed that CXCR4 inhibitor-resistant Env altered neutralization sensitivity to some NAbs (Fig. 3, Table S2).…”
Section: Discussionsupporting
confidence: 65%
“…As previous reports for other entry inhibitors (Berro et al, 2009;Pugach et al, 2008;Reeves et al, 2005; Yoshimura et al, 2014), we showed that CXCR4 inhibitor-resistant Env altered neutralization sensitivity to some NAbs (Fig. 3, Table S2).…”
Section: Discussionsupporting
confidence: 65%
“…Different escape pathways were also identified for HIV resistance to the peptidic entry inhibitor Fuzeon (52,53). However, Fuzeon escape did not coincide with resistance to other entry inhibitors (54). Broad cross-resistance against a structurally highly diverse panel of entry inhibitors appears unique to RSV F and may amount to a substantial obstacle in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to gp120-coreceptor interactions, substitutions in the gp41 N-HR and C-HR regions can influence the lifetime of the PHI (54,55). How such mutations impact the fusion …”
Section: Complex Synergy Mechanisms Of Hiv-1 Entry Inhibitorsmentioning
confidence: 99%